Adaptation and Initial Validation of Minimum Data Set (MDS) Mortality Risk Index to MDS Version 3.0. Issue 12 (18th October 2018) - Niznik, Joshua D.; Zhang, Song; Mor, Maria K.; Zhao, Xinhua; Ersek, Mary; Aspinall, Sherrie L.; Gellad, Walid F.; Thorpe, Joshua M.; Hanlon, Joseph T.; Schleiden, Loren J.; Springer, Sydney; Thorpe, Carolyn T.
Abstract : Objectives: To evaluate the predictive validity of an adapted version of the Minimum Data Set (MDS) Mortality Risk Index—Revised (MMRI‐R) based on MDS version 3.0 assessment items (MMRI‐v3) and to compare the predictive validity of the MMRI‐v3 with that of a single MDS item indicating limited life expectancy (LLE). Design: Retrospective, cross‐sectional study of MDS assessments. Other data sources included the Veterans Affairs (VA) Residential History File and Vital Status File. Setting: VA nursing homes (NHs). Participants: Veterans aged 65 and older newly admitted to VA NHs between July 1, 2012, and September 30, 2015. Measurements: The dependent variable was death within 6 months of admission date. Independent variables included MDS items used to calculate MMRI‐v3 scores (renal failure, chronic heart failure, sex, age, dehydration, cancer, unintentional weight loss, shortness of breath, activity of daily living scale, poor appetite, acute change in mental status) and the MDS item indicating LLE. Results: The predictive ability of the MMRI‐v3 for 6‐month mortality (c‐statistic 0.81) is as good as that of the original MMRI‐R (c‐statistic 0.76). Scores generated using the MMRI‐v3 had greater predictive ability than that of the single MDS indicator for LLE (c‐statistic 0.76); using the 2 together resulted in greater predictive ability (c‐statistic 0.86). Conclusion: The MMRI‐v3 is a useful tool in research and clinical practice that accurately predicts 6‐month mortality in veterans residing in Veterans Affairs NHs. Identification of residents with LLE has great utility for studying palliative care interventions and may be helpful in guiding allocation of these services in clinical practice.J Am Geriatr Soc 66:2353–2359, 2018 .